SISTEM INFORMASI PENGELOLAAN SURAT KEPUTUSAN PADA UNIVERSITAS KOMPUTER INDONESIA - Dias Eka Fredianto; Deasy Permatasari (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2017)
In University Computer Indonesia there is a decision letters that is divided into two groups, namely the rector’s decision letter and decision letter of the foundation and of any decrees are divided into various types including the decision letter Policies, decision letter scholarships, decision letter the formation of the team, the decision letter post of structural, letter staffing decisions, decrees the establishment of the unit, a decision letter forming BEM and SMEs. And for each party receiving the decision letter did just a storage archive without putting it into a database and archival storage can allow data is damaged or lost and in search of data can take a long time.By seeing the current issue so I took the research topic